Preparation of silver nanoparticles with hydrophobic surface and their polyester based nanocomposite fibres with excellent antibacterial properties. (July 2014) - Sun, Bin; Hua, Beibei; Ji, Xiaohuan; Shi, Yuyuan; Zhou, Zhe; Wang, Qingmiao; Zhu, Meifang
Abstract : Silver nanoparticles with hydrophobic surface (HS-nano-Ag) of small size (<10 nm) and capped by 18 wt-% aliphatic acid were specially designed and prepared to improve their dispersibility in and phase compatibility with a polyester matrix. Polyester based nanocomposites with various HS-nano-Ag contents (0·1, 0·5, 1 and even 20 wt-%) were prepared by melt processing, and the effects of HS-nano-Ag additive on the structure and properties of polyester materials were investigated. The HS-nano-Ag had a fine and homogeneous dispersion in the polyester matrix as determined from transmission electron microscopy analysis. The polyester nanocomposites with lower content (≤500 ppm) of Ag had good spinnability, and the stress of the resulting fibres remained higher than 2·5 cN dtex −1 under non-optimised conditions. In addition, the resulting polyester fibres had good antibacterial rate (>96%) against Staphylococcus aureus and Escherichia coli when containing a low content of HS-nano-Ag (100 ppm).